Teacher's Feedback in Intensive Speaking Program - Madani La Bugi (Hasanuddin University, 2020)
Interaction plays a very important role in the classroom between students and teachers. This research was conducted to study the ways teachers initiate the interaction and give feedback to the students’ responses and was also meant to find out the students’ and teachers’ views towards their interaction in the classroom.Case study was conducted in an English institution mediating the teachers and students with different goals in the context of one student and one teacher in a class. This study employed observation to see the ways teachers initiate the interaction and give feedback to the students’ responses. Interview was undertaken to know students’ and teachers’ views towards their interaction in the classroom. There were 5 cases observed. This research was conducted following the series of data collection, data reduction, and data display. Interview was conducted to help gain the views from students and teachers.The result shows that the teachers initiated the interaction and gave feedback by employing all strategies with different frequency. However, student was also found to give initiation which gave much contribution to the continuation of the interaction during the teaching and learning process. It is really recommended for the next researchers to study on the non-linguistic strategies employed by teachers to initiate and give feedback since they were also found during the observation of this study.